Preparing the Leaders of Tomorrow: Learnings from a Two-Year Community of Practice in Fragility Fractures. Issue 1 (31st December 2022) - Murray, Suzanne; Langdahl, Bente; Casado, Enrique; Brooks, Keyla; Libanati, Cesar; Di Lecce, Livio; Lazure, Patrice
ABSTRACT: To facilitate the development of leadership competencies in a multidisciplinary group of 18 emerging bone experts from 6 European Countries and Brazil, to face future scenarios in the evolving field of fragility fractures, and to support secondary fracture prevention and improve patient outcomes. Changes brought by the COVID-19 pandemic have further highlighted this need. A 2.5-year community of practice (CoP) programme was established with two senior bone experts acting as mentors. The content was adapted during the COVID-19 pandemic. The education impact of the programme was assessed using an ethics-approved mixed-method design consisting of multiple sources of qualitative and quantitative data collected longitudinally. Quantitative data were analysed descriptively. Qualitative data underwent a thematic analysis. After participating in the programme, participants reported increased interprofessional collaboration and communication skills, better understanding of health economics and negotiation, application of adult learning principles to their work setting, development of competencies to critically appraise guidelines, enhanced abilities to facilitate behaviour change in others, and improved confidence leading their team through crisis situations. Although time was required for some physicians to get accustomed to the CoP concept and develop trust with other members, it was described as a beneficial real-world learning experience. An educational real-world CoP programme was effective in enhancing leadership competencies among future leaders in the bone field to improve care of fragility fracture patients. The results presented could guide the development of other CoPs in fragility fracture care as leadership competencies are increasingly required in that field.